2009
DOI: 10.1021/jf8034447
|View full text |Cite
|
Sign up to set email alerts
|

Affinity of Microbial Transglutaminase to αs1-, β-, and Acid Casein under Atmospheric and High Pressure Conditions

Abstract: Kinetics for the reaction of microbial transglutaminase (MTG) with individual caseins in a TRIS-acetate buffer at pH 6.0 was evaluated under atmospheric pressure (0.1 MPa) and high pressure (400 MPa) at 40 °C. The reaction was monitored under the following limitations: The kinetics from the initial velocities was obtained from nonprogressive enzymatic reactions assuming that the individual catalytic constants of reactive glutamine residues are represented by the reaction between MTG and casein monomers. Enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…To determine the values of the kinetic parameters (V max , K m , and k ca ) , we plotted linear regressions results using the Hanes diagrams developed by Menéndez et al [30]. The MTGase-catalyzed reaction with individual caseins was investigated at various substrate concentrations (from 2 to 12 mg/mL).…”
Section: Enzyme Kinetics Of Mtgase Reacting With Individual Caseinsmentioning
confidence: 99%
“…To determine the values of the kinetic parameters (V max , K m , and k ca ) , we plotted linear regressions results using the Hanes diagrams developed by Menéndez et al [30]. The MTGase-catalyzed reaction with individual caseins was investigated at various substrate concentrations (from 2 to 12 mg/mL).…”
Section: Enzyme Kinetics Of Mtgase Reacting With Individual Caseinsmentioning
confidence: 99%
“…SEC column materials differ in composition and pore volume. The column most frequently used for studying cross-linked casein is Superdex 200, e.g., [30,44,47,48,54,100,115,131,[134][135][136][137][138][139][140][141][142][143][144][145][146][147][148], which is provided by GE Healthcare (Uppsala, Sweden). The column material is based on agarose/dextran with a ratio of pore volume to void volume of V i /V o = 1.7 and exhibits a fractionation range from 10 to 600 kg/mol for globular proteins [128].…”
Section: Separation Principlementioning
confidence: 99%
“…Despite the numerous reaction sides of casein, Menéndez et al [140] assumed TGase-catalysed cross-linking to be a single substrate reaction of monomers into polymers at short incubation times (<15 min) and fitted their data to Michaelis-Menten enzyme kinetic (see [151]). The kinetic data revealed that maximum reaction velocity is highest for cross-linking of β-casein, followed by non-micellar acid casein and α S1 -casein; however, the enzyme had the highest affinity to acid casein, which was explained by the presence of κ-casein.…”
Section: Literature Review Of Studies On Cross-linked Caseinmentioning
confidence: 99%
“…41 The catalytic activities of TGm1 variants toward proteins were examined using β-casein (Macklin, Shanghai, China) as the substrate according to a previous study. 42 β-Casein was diluted to 3 mg/mL with the Tris-acetate buffer (100 mM, pH 7) containing 10 mM NaCl. The catalytic reaction at 40 °C was initiated by adding each TGm1 variant at a final concentration of 0.005 mg/mL.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%